The life and times of the peanut - Micucci, Charles (Boston : Houghton Mifflin, 1997)
Examines the history and statistics of peanuts, their agriculture and influence.
Includes bibliographical references (p. [2]).
G8
Keywords: Peanuts -- Juvenile literature; Peanuts